Women in civil based society: a case study of Persekutuan Perkumpulan Wanita Sarawak (PPWS) / Noorfadhleen Mahmud, Azlina Bujang and Nadrawina Isnin - Mahmud, Noorfadhleen; Bujang, Azlina; Isnin, Nadrawina (2012)
Women in civil based society can be define as women’s movement, women's pressure group or interest group, women’s association and women’s NGOs. It is an institution in civil society to address women’s issues which the government has not been able to manage. It is a mediator whereby women issues can be brought to the attention of government. Since independence, more than 50 women’s NGOs have been established in Sarawak and this is an important indication that Sarawak women have realized their important roles and contribution to the society. The study used qualitative method that emphasize on personal interview and research on secondary data. The study focused on the role and contribution of Persekutuan Perkumpulan Wanita Sarawak (PPWS) and other selected women’s NGOs as the unit to be analyzed to seek the truth of challenges that inhibit Sarawak women to participate in civil based society. PPWS is one of the oldest women NGOs established and has played a vital role in coordinating all women's NGOs in Sarawak.